Concurrence of Anorexia Nervosa and Noonan Syndrome. (24th September 2013) - Arvaniti, Aikaterini; Samakouri, Maria; Keskeridou, Flora; Veletza, Stavroula
Summary Noonan syndrome (NS) is a genetic disease inherited in an autosomal dominant mode; it presents significant genetic heterogeneity and varying penetrance. Mutations have been identified in several genes, and they account for 75% of all known cases. The majority of reported mutations are localized on PTPN11 gene, which encodes the non‐receptor type protein tyrosine phosphatase SHP‐2. Diagnosis, however, is mainly established after clinical examination. Anorexia nervosa (AN) is an eating disorder characterized by fear of gaining weight, refusal to maintain normal body weight and distorted perceptions of body image or body shape. AN is independently predicted by female sex and feeding problems in childhood, whereas NS symptoms include feeding difficulties. No comorbidity between NS and AN has been reported to date. The authors reported the case of a 38‐year‐old female patient with AN who met the van der Burgt criteria for NS with confirmed (a) comorbidity of AN and NS and (b) the absence of the most common mutation in PTPN11 and presence of a novel T > A transversion within intron 8–9. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.